Influence of SCA on clinical outcomes and cervical alignment after laminoplasty in patients with multilevel cervical spondylotic myelopathy - Wang, Zheng (J Orthop Surg Res, 2021)
BACKGROUND: To study the impact of changes in spino-cranial angle (SCA) on sagittal alignment and to investigate the relationship between SCA and Neck Disability Index (NDI) scores after laminoplasty (LP) MATERIAL AND METHODS: In total, 72 patients with multilevel cervical spondylotic myelopathy (MCSM) after laminoplasty (LP) were retrospectively enrolled. Based on the optimal cut-off values of preoperative SCA, patients were classified into low SCA and high SCA groups. Radiographic data were measured, including spino-cranial angle (SCA), T1-slope (T1s), C2–7 lordosis (CA), T1s minus CA (T1sCA), and C2–7 sagittal vertical axis (cSVA). JOA and NDI scores were both applied to assess postoperative and follow-up clinical efficacy. Pearson correlation coefficient and linear regression analysis were respectively calculated between radiographic data and between SCA and NDI. RESULTS: The preoperative SCA was significantly correlated with T1s (r = − 0.795), CA (r = − 0.857), and cSVA (r = 0.915). A receiver operating characteristic (ROC) curve model predicted a threshold of SCA (value of 85.2°). At the follow-up period, patients with lower SCA had a higher T1s and CA and a lower cSVA, simultaneously accompanied by greater △T1s, △CA, and △cSVA. The linear regression model demonstrated that SCA in the higher group was positively correlated with NDI, and patients with higher SCA had worse NDI scores (pre: p < 0.001; post: p < 0.001; F/U: p = 0.003) and greater changes of NDI (post: p < 0.010; F/U: p = 0.002). CONCLUSION: SCA may be a good predictor of evaluating sagittal balance and planning surgery. Changes in sagittal alignment in the low SCA group were affected more easily, and a higher SCA was associated with worse quality of life. Laminoplasty could be a good choice for patients with lower SCA.